PERSEPSI SISWA TERHADAP EFEKTIVITAS PROSES BELAJAR MENGAJAR DAN HUBUNGANNYA DENGAN HASIL BELAJAR MATEMATIK - Hasibuan, May Fitriana (Information Technology and Science (ITScience), 2019)
Mathematics as one part of education that must be learned by each student in formal institutions. Mathematics is also one of the fields of study that has an important role and many of us meet in everyday life. So there is no doubt that mathematics is one of the pinnacles of intellectual glory. Etymologically the perception comes from English, namely